Rapid, high-titer biosynthesis of melanin using the marine bacterium Vibrio natriegens - Smith, Aaron D.; Tschirhart, Tanya; Compton, Jaimee; Hennessa, Tiffany M.; VanArsdale, Eric; Wang, Zheng (Frontiers in Bioengineering and Biotechnology, 2023)
Melanin is one of the most abundant natural biomolecules on Earth. These macromolecular biopolymers display several unique physical and chemical properties and have garnered interest as biomaterials for various commercial and industrial applications. To this end, extensive research has gone into refining methods for the synthesis and extraction of melanin from natural and recombinant sources. In this study, we developed and refined a procedure using a recombinant microbial system for the biosynthesis of melanin using the tyrosinase enzyme Tyr1 and tyrosine as a substrate. Using the emergent microbial chassis organisms Vibrio natriegens, we achieved maximal yields of 7.57 g/L, and one of the highest reported volumetric productivities of 473 mg L -1 h -1 with 100% conversion rates in an optimized, minimally defined medium. Additionally, we identified and investigated the use of a native copper responsive promoter in V. natriegens for stringent regulation of heterologous protein expression as a cost effective alternative to traditional IPTG-based induction. This research represents a promising advancement towards a green, rapid, and economical alternative for the biomanufacture of melanin.